2018
DOI: 10.1038/s41598-018-24678-4
|View full text |Cite
|
Sign up to set email alerts
|

aPKCζ-dependent Repression of Yap is Necessary for Functional Restoration of Irradiated Salivary Glands with IGF-1

Abstract: Xerostomia and salivary hypofunction often result as a consequence of radiation therapy for head and neck cancers, which are diagnosed in roughly 60,000 individuals every year in the U.S. Due to the lack of effective treatments for radiation-induced salivary hypofunction, stem cell-based therapies have been suggested to regenerate the irradiated salivary glands. Pharmacologically, restoration of salivary gland function has been accomplished in mice by administering IGF-1 shortly after radiation treatment, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(85 citation statements)
references
References 64 publications
0
85
0
Order By: Relevance
“…While most current treatments for salivary gland dysfunction target expansion of residual salivary acinar cells to repair damaged tissue, regenerative therapy with stem cells is a novel and promising therapeutic approach to replace damaged salivary glands (Carpenter and Cotroneo, 2010;Lombaert et al, 2017;Ogawa and Tsuji, 2017). Several studies have identified and characterized subsets of endogenous salivary progenitor cells that can be exploited to promote tissue regeneration (Lombaert et al, 2008;Chibly et al, 2014Chibly et al, , 2018Pringle et al, 2016;Emmerson et al, 2018;Weng et al, 2018). The use of modified fibrin hydrogels (Nam et al, 2019a), layered sheets of isolated salivary gland cells released from thermoresponsive culture dishes (Nam et al, 2019b) and salivary organoid cultures generated from embryonic pluripotent stem cells (Tanaka et al, 2018) have been explored as regenerative therapies for damaged salivary glands.…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…While most current treatments for salivary gland dysfunction target expansion of residual salivary acinar cells to repair damaged tissue, regenerative therapy with stem cells is a novel and promising therapeutic approach to replace damaged salivary glands (Carpenter and Cotroneo, 2010;Lombaert et al, 2017;Ogawa and Tsuji, 2017). Several studies have identified and characterized subsets of endogenous salivary progenitor cells that can be exploited to promote tissue regeneration (Lombaert et al, 2008;Chibly et al, 2014Chibly et al, , 2018Pringle et al, 2016;Emmerson et al, 2018;Weng et al, 2018). The use of modified fibrin hydrogels (Nam et al, 2019a), layered sheets of isolated salivary gland cells released from thermoresponsive culture dishes (Nam et al, 2019b) and salivary organoid cultures generated from embryonic pluripotent stem cells (Tanaka et al, 2018) have been explored as regenerative therapies for damaged salivary glands.…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…Some prevailing theories in the field include damaged stem and progenitor cell (SPC) pools, defective secretory pathways, irregular inflammatory responses, and cell death [4][5][6][7][8][9]. Recent studies have shown that the structural integrity of the epithelium is altered and that these defects are associated with aberrant apical-basolateral polarity, loss of lateral junctions and disorganized cytoskeletal structure [10][11][12][13]. In particular, radiation damage reduces the activity of an apical polarity protein, atypical protein kinase zeta (aPKCz), in both SPCs and acinar cells resulting in hyperproliferation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the structural integrity of the epithelium is altered and that these defects are associated with aberrant apical-basolateral polarity, loss of lateral junctions and disorganized cytoskeletal structure [10][11][12][13]. In particular, radiation damage reduces the activity of an apical polarity protein, atypical protein kinase zeta (aPKCz), in both SPCs and acinar cells resulting in hyperproliferation [11,12]. Loss of aPKCz in the SPCs promoted nuclear translocation of Yes-associated protein (Yap), a transcriptional co-activator regulated by Hippo signaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…A caveat is that the DNA label will be retained by cells undergoing terminal differentiation, as well as by potential quiescent stem cells . Consistent with this, LRCs are found in all parenchymal compartments of the salivary glands , and can colocalize with markers of differentiated acinar or duct cells . Due to the low rate of cell turnover in the adult salivary gland, cells labeled during an earlier proliferative phase will be retained for long periods.…”
Section: Quiescent or Proliferative Stem Cellsmentioning
confidence: 79%
“…Labeling done during embryonic development identified LRCs after long‐term chase that had low proliferative potential in vitro and did not actively proliferate following injury . In contrast, labeling postnatally followed by a shorter chase identified LRCs that showed self‐renewal capacity in vitro and in vivo proliferation in response to injury . Labeling at embryonic or postnatal stages likely marked different populations of dividing cells.…”
Section: Quiescent or Proliferative Stem Cellsmentioning
confidence: 99%